The executive functions in primary insomniacs: literature review - Ferreira, Olivia Dayse Leite; Moraes de Almondes, Katie (Perspectivas en Psicología, 2014)
The primary insomnia can cause a great impact on the individuals' cognitive functioning, especially related to the called executive function. Therefore, this work aimed to review the major studies in literature that addressed the relation between primary insomnia and the executive functions in young adults. For this purpose, it was conducted a bibliographical survey regarding publications of the last twenty years (1993-2013), in electronic databases: PubMed, PsycInfo and Scielo. Eleven scientific articles were selected by inclusion and exclusion criteria set. Most part of the studies did not identify deficits in the executive function modes in adults with primary insomnia. However, it was observed that there was a mismatch from the methodological perspective between studies, related to the variability of the methods used, the types of tests and diagnostics criteria for primary insomnia.